REFLEXIVE PROJECT MANAGEMENT OF THE STRATEGIC DEVELOPMENT - Вакуленко, Валентина Петрівна; Курносенко, Лариса Володимирівна (Eastern-European Journal of Enterprise Technologies, 2013)
Reflexive management refers to the re-interpretation by all the members of management of their own development experience, project development, organization, and on this basis to absorb new development opportunities. Considering the lack of theoretical and methodological foundation the reflexive management up to the present has not been systematically used in the practice of strategic management. There are many social, political, and economic phenomenon and processes which may be interpreted as such that use reflexive management. As far as there are many methods of strategic management, forecasting and predicting the future, however, which using is impossible without reflection. One of the methods that are commonly used in the practice of management, the method of predicting the future, the construction of future events is a method of foresight. Foresight is a systematic, based on the participation of stakeholders, the process of gathering information about the future which aim is a rapid decision-making and common action. According to the concept of foresight FOR-LEARN, foresight is defined by a triangle: thinking about the future - a discussion of the future - building the future. Using reflection in the process of foresight provides a chance to approach, to combine the freedom of thought and communication with effective organization of management.